The effectiveness of the European agricultural quality policy: a price analysis - Bardají, I.; Iráizoz, B.; Rapún, M. (Spanish Journal of Agricultural Research, 2009)
The European rural development policy, the second pillar of the Common Agricultural Policy, is currently playing an increasing role. One of its key instruments is the support for quality standards through Protected Geographical Indications (PGI). The analysis presented in this article investigates prices for two varieties of beef (PGI and non-PGI). The research setting is a specific area in northern Spain, where "Ternera de Navarra" (Navarra beef) is produced. The results show that quality production systems achieve higher and more stable prices in the long term. Another major point emerging from the analysis, given the nature of the beef production sector, is that the PGI product is better able to stand up to consumer confidence crises, such as that triggered by the bovine spongiform encephalopathy outbreak.